Large L-shape Fit Spectrum Allocation for Elastic Optical Network with Spectrum Slicing - Kaito Akaki; Praphan Pavarangkoon; Nattapong Kitsuwan (My University, 2021)
A slicing and stitching technology has been invented to relax the consecutive constraint of spectrum slot allocation in elastic optical network (EON). This technology splits a spectrum band into several signal bands, called optical components, by making a copy of the original spectrum band and filtering out an unwanted signal on each spectrum band. The remaining optical components are injected into a transmission channel. At the destination, the optical components are recovered by using phase preserving wavelength conversion. Therefore, a request is able to allocate to dis-consecutive groups of slots. A conventional spectrum allocation scheme with this technology adopts slicing devices, called spectrum slicers, at only a source node. There is a problem of allocation patterns due to lack of flexibility since slicing at intermediate nodes is not considered. In this paper, we propose a spectrum allocation scheme considering slicers at both source node and intermediate nodes. Performance of the proposed scheme is evaluated by a computer simulation. The results show that the proposed scheme with 20 slicers reduces 45% of request blocking probability compared to the conventional scheme in COST239 topology when the traffic is 300 Erlang.
Keywords: Advanced Optical Network Technologies; Optical Network Technologies; Advanced Photonic Communication Systems